1999
DOI: 10.1093/hmg/8.4.575
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of a Secreted Frizzled-Related Protein that is Expressed by the Retinal Pigment Epithelium

Abstract: The Wnt/frizzled cell signaling pathway has been implicated in the determination of polarity in a number of systems, including the Drosophila retina. The vertebrate retina develops from an undifferentiated neuroepithelium into an organized and laminated structure that demonstrates a high degree of polarity at both the tissue and cellular levels. In the process of searching for molecules that are preferentially expressed by the vertebrate retinal pigment epithelium (RPE), we identified secreted frizzled-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
1
4

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 49 publications
3
53
1
4
Order By: Relevance
“…However, Wnt genes are expressed at very low levels compared with Mfz or Sfrp genes. In contrast to Chang et al, who showed Sfrp-2 expression in the INL of the bovine retina (Chang et al, 1999), we find that Sfrp-2 expression is down-regulated in the murine retina after P7. Similarly, Rattner et al (1997) reported that Sfrp-1 transcripts are restricted to the ciliary margin and lens in the adult mouse eye; however, we find that Sfrp-1 transcripts are also present in the neural retina at this stage.…”
Section: Wnt Signaling In the Perinatal And Adult Retinacontrasting
confidence: 99%
See 1 more Smart Citation
“…However, Wnt genes are expressed at very low levels compared with Mfz or Sfrp genes. In contrast to Chang et al, who showed Sfrp-2 expression in the INL of the bovine retina (Chang et al, 1999), we find that Sfrp-2 expression is down-regulated in the murine retina after P7. Similarly, Rattner et al (1997) reported that Sfrp-1 transcripts are restricted to the ciliary margin and lens in the adult mouse eye; however, we find that Sfrp-1 transcripts are also present in the neural retina at this stage.…”
Section: Wnt Signaling In the Perinatal And Adult Retinacontrasting
confidence: 99%
“…The expression of Mfz and Sfrp transcripts in the adult eye has been reported previously Rattner et al, 1997;Chang et al, 1999), and we extend those findings by showing the localization of Wnts, in the mouse neural retina at perinatal and adult stages. However, Wnt genes are expressed at very low levels compared with Mfz or Sfrp genes.…”
Section: Wnt Signaling In the Perinatal And Adult Retinasupporting
confidence: 89%
“…These proteins are receptors for Wnt family members. The function of SDF-5 is not clear, although it has been suggested that when over-expressed in breast cancer cells it regulates apoptosis of the cells, possibly by way of ß-catenin (22,23). Little is available with regard to the expression of these new SDFs in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Secretory Frps were independently isolated from bovine, Xenopus, mouse, rat and human by different laboratories (Hoang et al, 1996; Leyns et al, 1997; Rattner et al, 1997;Wang et al, 1997;Wolf et al, 1997;Zhou et al, 1998;Chang et al, 1999;Yam et al, 1999;Katoh, 2001). The precise interaction of each Frp protein in modulating Wnt signaling remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%